Fatigue of swollen elastomers. (May 2015) - Loo, Mei Sze; Le Cam, Jean-Benoît; Andriyana, Andri; Robin, Eric; Afifi, Amalina Muhammad
Highlights: The fatigue behaviour of swollen nitrile rubbers at the same degree of swelling is investigated. Fatigue tests are carried out under uniaxial loading conditions. The fatigue lifetime is found longest for dry, followed by swollen in B0 and B100. Loading conditions are found to have no effect on the crack initiation and propagation zone. Fatigue cracks initiate at the surface in dry and swollen rubbers. Abstract: The compatibility of the properties of elastomer with conventional diesel fuel has made it favourable in many engineering applications. However, due to global energy insecurity issues, there is an urgent need to find alternative renewable sources of energy as replacements to conventional diesel. In this respect, biodiesel appears to be a promising candidate. Hence, research into the compatibility and fatigue characteristics of elastomers exposed to biodiesel becomes essential. The present paper introduces the first attempt to investigate the effect of different solvents on the fatigue of swollen elastomers. The filled nitrile rubbers are immersed in the palm biodiesel and conventional diesel to obtain the same degree of swelling prior to the application of uniaxial fatigue loading. Field Emission Scanning Electron Microscopy (FESEM) analysis is carried out to observe the fracture surfaces. Stretch-N curves are plotted to illustrate the fatigue life duration. These curves showed that the fatigue lifetime of rubber is the longest for dry rubber and the least for rubber swollen in biodiesel. FESEM micrographs reveal that the loading conditions have no effect on the crack initiation and propagation patterns regardless of the swelling state.